Model-Predictive-Control-Based Flexible Arc-Suppression Method for Earth Fault in Distribution Networks - Wei-Qiang Qiu; Mou-Fa Guo; Geng-Jie Yang; Ze-Yin Zheng (IEEE Access, 2019)
Traditional arc-suppression devices have a weak effect on the arc-extinguishing result of earth fault because of increased active and harmonic components of fault current. To solve the problem, in this paper, a flexible arc-suppression device based on a three-phase cascaded H-bridge (CHB) converter with auxiliary sources is further developed; on this basis, an arc-suppression method based on the improved finite control set model predictive control is proposed. The proposed approach, which uses a combination of two voltage levels in a sampling period to reduce the steady-state current error, controls the CHB converter to inject compensation current into the distribution network. Taking into account the reduction of switching losses and balancing heat in each H-bridge cell, a novel method that causes the switching transitions to be distributed evenly among the H-bridge cells is proposed to select the optimal switching combination. The tracking capability of the improved control method is analyzed, and the parameters affecting the arc-suppression performance are obtained. The simulation and experimental results show that the proposed method achieves an excellent performance of suppressing fault current and extinguishing arc. Moreover, the balance of switching transitions is also achieved.